ESTIMATION OF THE ABUNDANCE AND DISTRIBUTION OF RARE EARTH ELEMENTS IN SOIL AROUND KADUNA REFINING AND PETROCHEMICAL COMPANY USING NUCLEAR TECHNIQUE - Onoja, Michael A.; Bukar, P. H.; Omeje, C. U.; Adamu, A. M. (FUDMA JOURNAL OF SCIENCES, 2020)
Instrumental neutron activation analysis (INAA) technique was used to investigate the abundance and distribution of rare earth elements (REE) in soil around Kaduna Refinery. The aim of the study is to assess the rare elements potential of Nigeria for economic exploitation. Five REEs (La, Dy, Eu, Yb, and Lu) were detected in varying concentrations ranging from a minimum of 0.6 Âµg/g (Lu) to a maximum of 249.0 Âµg/g (La). The elements existed with trends consistent with the natural pattern of REEs in soil, showing significant Eu and Dy anomalies which characterize upper plains and flood plains. The levels of REEs in soil in the study area were generally slightly above background levels, with minimal (La, Dy, and Eu), moderate (Yb), and significant (Lu) enrichments and trending: Lu ËƒYb Ëƒ Eu Ëƒ Dy Ëƒ La. The abundance of the REEs investigated cannot establish a potential of Nigeria for economic exploitation of the mineral, hence, rare earth project in the study area is not viable at the moment.
Keywords: INAA, REE, abundance, soil, Kaduna Refinery